Identification and characterization of the Epstein-Barr virus receptor on human B lymphocytes and its relationship to the C3d complement receptor (CR2). - Nemerow, G R (1985)
In pursuing studies on the early events in the infection of human B cells by Epstein-Barr virus (EBV), we examined the host cell attachment phase with a panel of B-cell-specific monoclonal antibodies. One of the monoclonal antibodies, OKB7, directly blocked the attachment of purified EBV to B lymphocytes in the absence of a second anti-immunoglobulin antibody and thereby prevented EBV infection of tonsil and peripheral blood B cells. Although earlier studies have shown a close association of the EBV and complement receptor (CR2), an anti-CR2 monoclonal antibody, anti-B2, did not directly block the binding of EBV to B cells. A comparison of the structures recognized by these monoclonal antibodies on various cell types and their functional and physiochemical properties was undertaken. Flow cytometric analysis revealed that the molecules detected by OKB7 and anti-B2 were coexpressed to the same extent on B cells but were not expressed on T-cell lines. OKB7 and anti-B2 both immunoprecipitated a 145,000-molecular-weight membrane protein with an isoelectric point of 8.2 from membrane extracts of Raji lymphoblastoid cells. OKB7 and, to a lesser extent, anti-B2 directly blocked the attachment of C3d,g-coated fluorescent microspheres and sheep erythrocytes bearing C3d to B cells, indicating that these antibodies also react with CR2. These studies indicate that the EBV-CR2 receptor is a single membrane glycoprotein which possesses multiple antigenic and functional epitopes.